Dynamic of intentional homicide cases in Presidente Hayes: State’s jurisdictional response in the 14th Judicial Area, according to judicial (Legal journal - Research in Legal and Social Sciences, 2020)
Since its establishment, in 2015, until april 2019, the 14th Judicial Area’s Trial Court, located in the city of Villa Hayes, department of Presidente Hayes, recorded sixty three convictions for intentional homicide cases, while seven cases were acquitted. This articles covers the dynamic of the cases in the Department of Presidente Hayes during the past three years. For better understanding of the context of intentional homicides and their characteristics, this paper analyses the final judments provided by the statistics department of the mentioned city’s Judiciary, by means of registrations in a data table that contains information about the perpetrators, victims, motives, and specific characteristics of each case, comparing the explanations of the cases and their dynamics, to the existing theories on the case. The findings determine the existence of convictions of 15 or more years of imprisonment, and others even with the so called “security measures”.
Keywords: conviction; homicide; perpetrators; victim